General Practitioners and Chronic Non-Malignant Pain Management in Older Patients: A Qualitative Study - Mary-Claire Kennedy; Martin C. Henman; Gráinne Cousins (MDPI AG, 2016)
Chronic non-malignant pain (CNMP) is commonly managed by General Practitioners (GPs) in primary care. Analgesics are the mainstay of CNMP management in this setting. Selection of medications by GPs may be influenced by micro factors which are relevant to the practice setting, meso factors which relate to the local or regional environment or macro factors such as those arising from national or international influences. The aim of this study is to explore influences on GP practises in relation to pain management for older adults with CNMP. Semi-structured interviews were conducted with 12 GPs. Transcripts were organised using the Framework Method of Data Management while an applied thematic analysis was used to identify the themes emerging from the data. Clinical considerations such as the efficacy of analgesics, adverse effects and co-morbidities strongly influence prescribing decisions. The GPs interviewed identified the lack of guidance on this subject in Ireland and described the impact of organisational and structural barriers of the Irish healthcare system on the management of CNMP. Changes in practice behaviours coupled with health system reforms are required to improve the quality and consistency of pharmacotherapeutic management of CNMP in primary care.